Working memory: Differences between young adults and the aged in listening tasks * - Maria Isabel d'Ávila Freitas; Ariella Fornachari Ribeiro; Márcia Radanovic; Leticia Lessa Mansur (Dementia & Neuropsychologia)
Abstract Working memory is a system with a limited capacity which enables the temporary storage and manipulation of the information necessary for complex cognitive tasks. Numerous studies have suggested that performance in these tasks is related to age where older adults have a lesser performance than the young. Objective: To analyze the processing functions of working memory in a listening task. Method: 59 educated participants aged between 19 and 76 years having no memory complaints were divided into two groups (young and aged adults). The test administered was the adapted Listening Span, in which the subject listens to a sentence, judging whether it is true or false and, concomitantly, stores the last word of each sentence for later evocation. Results: In the judgment task, performance of both groups approached to a similar average. Results of sentence recall demonstrated that with the increase in number of sentences at each level, performance of both groups declined. In the blocks of sentences 1 and 2 at level 1, all participants performed similarly. In the block of sentences 3, at level 1, there was a difference between the young and the aged. From this level onward (retention of 3 to 5 items), the aged and the young differed significantly. Conclusions: An increase in the number of sentences diminished participants' performance of temporary storage in the recall tasks, while not interfering in the processing of sentences during judgment. The difference between the young and the aged became more accentuated as item retention demands increased.